Implementasi Model PBL Diferensiasi Berdasarkan Gaya Belajar Siswa Kelas V Pendidikan Kewarganegaraan dan Pancasila di Sekolah Dasar Negeri 4 Ranto Peureulak Aceh - Herawati, Herawati; Akmaluddin, Akmaluddin; Syarfuni, Syarfuni; Sari, Siti Mayang (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to determine the application of the Differentiated Problem-Based Learning (PBL) model in learning Pancasila and Civic Education regarding socio-cultural diversity in Indonesia by considering student learning styles. This research was conducted using qualitative descriptive research method in grade V at SD Negeri 4 Ranto Peureulak. Data on students' learning styles were collected using observation techniques through questionnaires. Data analysis is carried out qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results showed a diversity of student learning styles, with most students identifying visual learning styles. In addition, the application of differentiated PBL has a positive impact because it can reveal potential according to their interests to provide a more meaningful learning experience for students